Analisis Web Site e-Government Instansi Pemerintah PROPINSI Jawa Tengah - Dena Evi Susiani; Setya Marsudi (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
In more and more countries across the world it is becoming required for government and other public service websites to be based on standards and follow accessibility guidelines. Unfortunately, many web agencies do not seem to be interested in building high-quality websites, using best practices, or making sure the sites they build are accessible to all. Web standards do not equal accessibility, but using web standards is an integral part of building an accessible website, and the validation results usually indicate if any effort at all has been spent on making a site accessible. Keywords: E-government, web-site performance, internet